2006
DOI: 10.1016/j.jaci.2006.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Oral pathogens and allergic disease: Results from the Third National Health and Nutrition Examination Survey

Abstract: Colonization of the oral cavity by bacteria and other microbes might play a protective role in the etiology of allergic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 29 publications
4
37
2
2
Order By: Relevance
“…Several studies have identified a positive association between serum levels of antibodies to P. gingivalis and cardiovascular disease risk in humans (3,28,29), although recent observations of inverse relationships between serum P. gingivalis antibody levels and asthma prevalence and between the incidences of periodontitis and allergic respiratory diseases (2,10) suggest that not all extra-oral effects of this bacterium may be deleterious. Furthermore, the improvement in oral hygiene in recent decades coincides with the increase in asthma prevalence in developed nations (1,16), suggestive of a potentially causative relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified a positive association between serum levels of antibodies to P. gingivalis and cardiovascular disease risk in humans (3,28,29), although recent observations of inverse relationships between serum P. gingivalis antibody levels and asthma prevalence and between the incidences of periodontitis and allergic respiratory diseases (2,10) suggest that not all extra-oral effects of this bacterium may be deleterious. Furthermore, the improvement in oral hygiene in recent decades coincides with the increase in asthma prevalence in developed nations (1,16), suggestive of a potentially causative relationship.…”
Section: Discussionmentioning
confidence: 99%
“…7 Additionally, Arbes et al study showed that higher immunoglobulin G (IgG) to porphyromonas gingivalis were significantly associated with lower prevalences of asthma, wheeze, and hay fever. 8 These literatures supports the "hygiene hypothesis". Hygiene hypothesis stated in laymen's term that "cleanliness makes people more allergic".…”
Section: Introductionmentioning
confidence: 58%
“…The patients in these case report suffered from periodontitis with gingivitis, thus elimination of sub gingival plaque for reducing allergic symptoms was likely. Another contradictory study which conducted by Arbes et al 8 showed that higher IgG to porphyromonas gingivalis was related to the reduced prevalence to allergy. It could be explained that lower concentration of PgLPS which existed in chronic gingivitis or chronic periodontitis with gingivitis stimulates the toll-like receptor2 (TLR2), which increase the production of Th2 cytokines profile, i.e.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…8 This concept is also adopted by dental researchers. 9,10 on the other hand some believe that dental treatment increases anxiety which trigger asthma exacerbation. 11 Therefore, the concept of reducing asthmatic symptoms through elimination of oral infection is not easily accepted either by medical or dental professionals.…”
mentioning
confidence: 99%